The Role of Guardian Judges in Resolving Guardian Adhol Conflicts: Process and Outcome Analysis - Chloe Anne; Fajar Maulana; Rizky Aulia (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2022)
This research explores the role of guardian judges in resolving guardian adhol conflicts in religious courts, with a focus on analyzing the decision-making process and the outcomes of the intervention. Through a qualitative approach using the case study method, data was collected through in-depth interviews with judges, related parties and community members, as well as direct observation in religious courts and analysis of legal documents. The findings show that the judge's intervention was effective in overcoming the objections of the nasab guardian who were not based on sharia, as well as increasing public trust in the religious courts as an institution that is fair and responsive to the needs of the people. However, a small portion of the community criticized this intervention for its lack of sensitivity to local customs. This research recommends improving a holistic approach that considers the local cultural context without sacrificing the basic principles of Islamic law, as well as developing better communication strategies to explain the legal basis for judges' decisions to the public.